English Expressions and Terminologies Used for Reservation In PT. Raja Kamar Indonesia Jakarta - Sayyid Khairunas; Fuji Versia (LPPM Universitas Bina Sarana Informatika, 2018)
The aim of this final paper is to describe the use of English expression and terms used in hotel room reservation activities. As for the background of writing this paper is related to the importance of the use of English expression properly in accordance with standard operating procedure in a company oriented to the theory from experts. The writer uses a description method that begins with research in PT. Raja Kamar Indonesia. From the analysis of the data from this study contains of conversation and descriptions of terminologies in travel agent. The conclusion of this paper is that readers can understand the work activities of a telephone operator in the hotel reservation division. The activity of expression in English that is used is asking inquiry, reservation, amendment, cancellation and refund. In addition, knowledge of the terms in the reservation becomes inseparable from the activity of reservation work. The author hopes this paper can help readers to know more deeply related to science in the field of reservation.